Applied problems of microfluidics and nanofluidics : methodical recommendations for practical course and individual work - Kizilova, Nataliya N.; Кізілова, Наталія Миколаївна (Kharkiv : V.N. Karazin Kharkiv National University, 2023)
The basic knowledge of the micro/nanorheology and micro/nanofluidics are presented. The detailed solutions for the laminar flows of classical fluids between parallel plates and coaxial cylindrical tubes (both Poiseuille and Couette flows), laminar flow in an open inclined duct, Poiseuille flow in the channels with elliptic, circular, triangle and rectangle cross-sections and given. The corresponding solutions for the suspensions of microparticles (microfluids) and nanoparticles (nanofluids) of the Navier-Stokes equations with velocity slip boundary conditions of the first and second order, respectively, are presented for the most of the problems while the rest are proposed as individual tasks. For students of mathematical and physical faculties who study nanosciences, nanotechnologies and are interested in practical skills in solving applied problems of micro/nanofluidics.
Прикладні задачі мікрофлюідики і нанофлюідики : методичні рекомендації для практичних занять і самостійної роботи
Навчальне видання. Англійською мовою
Keywords: MATHEMATICS; SOCIAL SCIENCES; динаміка рідини; реологія; мікрофлюідика; нанофлюідика; нанотехнології; fluid dynamics; rheology; microfluidics; nanofluidics; nanotechnology